2015
DOI: 10.1111/are.12955
|View full text |Cite
|
Sign up to set email alerts
|

Dietary administration of natural immunostimulants on growth performance, haematological, biochemical parameters and disease resistance of Asian Sea bassLates calcarifer(Bloch, 1790)

Abstract: This study was aimed to address the promising evaluation of Cissus quadrangularis plant (stem) and lipopolysaccharide (LPS from bacteria) supplemented diets on innate immune response in Lates calcarifer fingerlings against Aeromonas hydrophila infection. Fingerlings were fed supplemented diets containing four different concentrations of C. quadrangularis (0.5, 1.0, 1.5 and 2.0 g kg À1 feed), LPS (25, 50, 75 and 100 mg kg À1 feed) and control (normal formulated diet) for 60 days. The fish fingerlings fed supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 51 publications
2
5
0
Order By: Relevance
“…Leucocytosis, also reported by Jantrarotai and Lovell (1990), attributed the cause of leucocytosis as a rejoinder to the necrosis of gastric glands. However, the aflatoxin group treated with lipopolysaccharides showed significant improvement in the haematological markers up to the average control level; these results were in harmony with Devakumar and Chinnasamy (2017), who stated that fish supplied with lipopolysaccharides revealed a substantial upsurge in erythrogram. Hannun and Linardic (1993) show the mechanism of how mycotoxins suppress an inflammatory response.…”
Section: Discussionsupporting
confidence: 81%
“…Leucocytosis, also reported by Jantrarotai and Lovell (1990), attributed the cause of leucocytosis as a rejoinder to the necrosis of gastric glands. However, the aflatoxin group treated with lipopolysaccharides showed significant improvement in the haematological markers up to the average control level; these results were in harmony with Devakumar and Chinnasamy (2017), who stated that fish supplied with lipopolysaccharides revealed a substantial upsurge in erythrogram. Hannun and Linardic (1993) show the mechanism of how mycotoxins suppress an inflammatory response.…”
Section: Discussionsupporting
confidence: 81%
“…Immunostimulants, which are feed additives derived from natural sources or synthetically, are capable of modulating the fish immune response and improving disease resistance. Therefore, people have begun to consider the immune stimulants used in the aquaculture industry [ 10 , 11 ]. Due to the low toxicity, small side effects, and little residue, increasing attention has been paid to herbs as environmentally friendly immunostimulants, and many studies have shown that herbs play a positive role in the prevention and treatment of fish diseases [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have explored the effects of plant or herbal, such as garlic, hirami lemon, and leaf meal, extracts as feed additives on the rearing performance of L. calcarifer , and positive effects in terms of growth and immunity have been observed (faster growth, higher disease resistance. and lower mortality rates) [ 4 , 9 , 10 ]. In this study, G. uralensis was used as the feed additive to test the immune responses of L. calcarifer .…”
Section: Introductionmentioning
confidence: 99%
“…These medicinal plants can either indirectly impact the cultured fish by strengthening the immune system and/or directly influence the host and its functions and processes to improve its physiological performance (Adel, Dawood, Shafiei, Sakhaie, & Hosseini Shekarabi, 2020; Awad, El‐Fiqi, Austin, & Lyndon, 2020; Gholamhosseini et al., 2020; Van Hai, 2015). Great efforts have been devoted to medicinal plants in regulating the fish immune response if either infection or stress happens (Devakumar & Chinnasamy, 2017; Ghehdarijani, Hajimoradloo, Ghorbani, & Roohi, 2016; Saeidi Asl, Adel, Caipang, & Dawood, 2017; Wang, Sun, Liu, & Xue, 2017). Furthermore, some studies reported that simultaneous use of supplements and medicinal plants can enhance development process and increase the effective rearing of aquatic animals (Adel, Abedian Amiri, Zorriehzahra, Nematolahi, & Esteban, 2015; Adel, Safari, Pourgholam, Zorriehzahra, & Esteban, 2015; Ahmadniaye Motlagh, Sarkheil, Safari, & Paolucci, 2020; Fadl et al., 2020; Zakęś et al., 2008; Zhang et al., 2020).…”
Section: Introductionmentioning
confidence: 99%